2022
DOI: 10.1371/journal.pone.0276727
|View full text |Cite
|
Sign up to set email alerts
|

How do international humanitarian aid workers stay healthy in the face of adversity?

Abstract: Background International humanitarian aid workers (iHAWs) are motivated strongly to travel abroad to help communities affected by war, famine, disaster and disease. They expose themselves to dangers and hardships during their field assignments. Despite working under such challenging circumstances, most workers remain healthy. The objective of the present study was to unravel the mechanism that enables workers to remain healthy under the same circumstances that affect these communities. We hypothesised that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Moreover, in accordance with our hypothesis, those with high levels of sense of coherence and coping self-efficacy pre-assignment are more likely to stay healthy (higher odds of membership of the ‘healthy/normative’ trajectory). Considering that high levels of pre-assignment sense of coherence and coping self-efficacy were associated with fewer symptoms of PTSD and anxiety ( 26 and Supplementary Appendix 1), it is less likely that those who score high on the CSE-7 and SOC have any need for health indicators to improve.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in accordance with our hypothesis, those with high levels of sense of coherence and coping self-efficacy pre-assignment are more likely to stay healthy (higher odds of membership of the ‘healthy/normative’ trajectory). Considering that high levels of pre-assignment sense of coherence and coping self-efficacy were associated with fewer symptoms of PTSD and anxiety ( 26 and Supplementary Appendix 1), it is less likely that those who score high on the CSE-7 and SOC have any need for health indicators to improve.…”
Section: Discussionmentioning
confidence: 99%
“…Because sense of coherence and meaningfulness are strong predictors of better health outcomes for AW (De Jong et al, 2022), the personal effect of the politicisation of humanitarian aid can challenge the resilience of AW. Aid organizations may create hostile environments by their mere presence, raising the security profile of AW (Fee et al, 2019).…”
Section: The Politics Of Aid Workmentioning
confidence: 99%
“…Sense of coherence is a determinant for well-being, and a key component for sense of coherence is meaningfulness (De Jong et al, 2022). For support AW lacking contact with beneficiaries, the absence of recognition and direct contact with aid recipients undermines sense of coherence (Thomas, 2016), individual motivation (Friesen, 2022), and meaning of work (Montaiuti, 2013); all factors that psychologically can aggravate existing strain.…”
Section: The Politics Of Aid Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, we investigated whether experiencing sexual harassment is associated with changes in psychosocial health between before and after a humanitarian field assignment and the use of health care following a field assignment. An earlier investigation based on the same sample indicated that other stressors than sexual harassment—namely field assignment-related stressors (e.g., health risks, high workload team stressors, security incidents)—were associated with higher mental health symptoms after an assignment (De Jong, Martinmäki, Te Brake, Kleber, et al, 2021). Therefore, we chose to control for the effect of field stressors in our analysis.…”
Section: Introductionmentioning
confidence: 97%